AN EMOTIONAL APPROACH ON CONSUMER SATISFACTION AND LOYALTY AT GANESHA OPERATION MAKASSAR - Putri Annisa R. Siduppa; Andi Anto Patak; Riny Jefri (International Journal of Business English and Communication, 2025)
This research aimed to identify the influence of an emotional approach on consumer satisfaction and loyalty to Ganesha Operation Makassar. This research uses qualitative methods to obtain data from respondents. Respondents in this study consisted of four employees and two students of Ganesha Operation Makassar. The results obtained from this research show that presenting an emotional approach in service greatly influences consumer comfort. This is because, through an emotional approach, a company can understand consumers from an internal and external perspective, and comfort can form consumer loyalty because a sense of trust has been formed in the company.